Oral Health Status, Severity of Malocclusion and Orthodontic Treatment Needs in Children with SHCN In Delhi-NCR - A Survey Based Study - Debnath, Sonvita; Ankita, Ankita; Gupta, Priyanka; Srivastava, Madhulika; Alam, Shabana Praveen; Shrivastava, Pallavi (Journal of Neonatal Surgery, 2025)
Background: Etiology of malocclusion is multifactorial and mainly determined by genetic factors and environmental factors. Improvement of oral health in a population begins with the collection of epidemiological data, which helps to understand the needs of our community to identify the high‑risk groups, then to carry out extensive planned treatment, prevention strategies and monitor the development of the situation over a period of years. Materials and methodology: The survey was conducted by examining 150 children with special healthcare needs in Delhi-NCR after obtaining consent form from their guardians/caregivers. WHO Oral Health Assessment Form (2013) for children was used for recording oral health status of the subjects. Information was collected through this form that included general information pertaining to study subjects like Name, Date of Birth, Age, and Gender. Examination was done using mouth mirror and Community Periodontal Index of Treatment Needs probe. The firmly established Index of Orthodontic Treatment need (IOTN) was utilized for the present study. IOTN has two parts; the Aesthetic (AC) and Dental Health (DHC) components. The Aesthetic Component consists of a scale of 10 color photographs showing different levels of dental attractiveness, grade 1 representing the most attractive and grade 10 the least attractive dentitions. And the Risk Of Malocclusion Assessment Index (ROMA INDEX) is an index to assess treatment priority in young patients was also used for treatment priority. Results: The distribution of the dental caries susceptibility among the study subjects was 17.1% involving primary dentition and 15.9% involving permanent teeth in the hearing disabled group, 39.5% involving primary dentition and 47.7% involving permanent teeth for the intellectually disabled, 22.5% involving primary dentition and 22.7% involving permanent teeth for the physically challenged study subjects and 20.9% involving primary dentition and 13.6% involving permanent teeth in visually impaired groups. According to the Index of Orthodontic Treatment Need, a larger proportion of participants were observed to have great need for orthodontic treatment need (47%) giving a score of IOTN 4. Also, it arose that patients at extreme risk require immediate intervention which is about 53.7% gives a score of ROMA GRADE 5. This result was found to be statistically significant. Conclusion: The results show a high prevalence of oral diseases, malocclusion, and orthodontic treatment needs in this population. Furthermore, the study suggests that early orthodontic treatment can help prevent traumatic dental injuries and improve overall oral health outcomes and increase the quality of life in this population. Therefore, it is crucial to develop programs and policies that promote oral health and orthodontic treatment for these children.